Drivers of continuance intention with mobile banking apps. Issue 1 (24th July 2019) - Poromatikul, Chayawan; De Maeyer, Peter; Leelapanyalert, Kannika; Zaby, Simon
Abstract : Purpose: The purpose of this paper is to examine the drivers of continuance intention with mobile banking apps, in a Thai context. The secondary objective is to examine if there are underlying segments that differ meaningfully in this regard. Design/methodology/approach: A structural equation model based on the European Customer Satisfaction Index is estimated. The data were obtained by conducting an online survey of mobile banking users in Thailand ( n =399). Findings: The top 3 factors directly affecting continuance intention toward mobile banking are satisfaction, trust and expectancy confirmation. Image and perceived risk also have an impact, although studies have reported that the latter is less impactful than the prior. One latent segment is more influenced by observable performance characteristics like confirmation and perceived quality, the other more by credence factors like trust and image. Practical implications: The study confirms the important role of satisfaction and expectancy confirmation in driving continuance. Somewhat unexpected is the high relative prominence of trust as a driver, at least in the Thai context. This is a "soft" variable managers should not dismiss. The identification of segments also points to potentially different treatment and actionable advice for managers. Originality/value: This paper adds to the scant body of empirical work on continuance intention with mobile banking. In light of the large investments in mobile banking capabilities being made, this is an under-researched area. This paper to the authors' knowledge is the first to study consumer heterogeneity in this context.